DIAGNOSTIK KONSEPSI SISWA PADA MATERI SUHU DAN KALOR - WINARTI, W; BUDIARTI, I S (Jurnal Ilmu Pendidikan Indonesia, 2020)
Diagnostics in physics learning are carried out to find the level of students’ conceptual understanding to the learning objectives. This study aimed to describe the conception of Madrasah Aliyah (MA) students in Special Region of Yogyakarta through diagnostic tests. Descriptive method was chosen to determine the level of students’ conceptual understanding on chapter temperature and heat. The sampling technique used was stratified random sampling so that 365 students from class X Natural Sciences were positioned as samples. Test was chosen as data collecting technique using the developed Temperature and Heat Test Higher Order Thinking Skills (THT-HOTS) instrument. The results of the study were the level of conceptual understanding achievement of Madrasah Aliyah (MA) students in the Special Region of Yogyakarta on chapter temperature and heat. The conceptual understanding of students was classified in the low category. It could be seen from the percentage of conceptual understanding achievement in four sub-chapter, namely: temperature and thermometer, heat and black principle, changes in the form of substances and expansion, which value were less than 20%.